A baseline-free damage detection approach based on distance compensation of guided waves. Issue 3 (December 2019) - Qiu, Jianxi; Li, Fucai; Abbas, Saqlain; Zhu, Yanping
The baseline signal in structural inspection based on guided waves is difficult to be obtained under varying environmental conditions. To guarantee the precision of damage identification, developing baseline-free damage detection methods is significant in practical structural monitoring work. Conventional instantaneous baseline measurement needs a large number of PZT transducers. In this paper, a novel damage identification method for plate-like structures based on distance compensation is proposed to overcome this shortage. Combining with the concept of instantaneous baseline measurement, pitch-catch pairs of different propagation distance can be compared together to reveal the health information of the measured paths. This method overcomes the drawback of instantaneous measurement, which can only monitor the paths of identical wave travelling distance. Both simulations and experiments are conducted to validate the proposed method. Using this method, the influence of damage size and classification on amplitude variation is discussed. Finally, a baseline-free damage imaging technique is developed based on amplitude loss ratio of the first arriving wave package. The result shows a good agreement of the predicted result and the real damage location.